Interconnectability of session-based logical processes - Toninho, Bernardo (2019)
This work is supported by NOVA LINCS (UID/CEC/04516/2013), EPSRC EP/K034413/1, EP/K011715/1, EP/L00058X/1, EP/N027833/1 and EP/N028201/1.